Postparasitic Micronutrient Deficiency In Children. - Rasulov S.K; Saidova F.S; Mamedov A.N; Ibragimov.S.T (Zien Journals, 2022)
Post-parasitic micronutrient deficiency is an umbrella term for a set of persistent symptoms that can develop in patients who have had intestinal parasites in children. The purpose of the work is to systematize data on the role of micronutrients in the diagnosis and treatment of intestinal parasitosis in children
Keywords: parasitosis; intestinal; micronutrient; umbrella